Astraeus – III. The environment and physical properties of reionization sources. Issue 1 (10th May 2021) - Hutter, Anne; Dayal, Pratika; Legrand, Laurent; Gottlöber, Stefan; Yepes, Gustavo
ABSTRACT: In this work, we use the astraeus (seminumerical rAdiative tranSfer coupling of galaxy formaTion and Reionization in N -body dArk mattEr simUlationS) framework that couples galaxy formation and reionization in the first billion years. Exploring a number of models for reionization feedback and the escape fraction of ionizing radiation from the galactic environment ( f esc ), we quantify how the contribution of star-forming galaxies (with halo masses M_ h10^8.2 M_ ) to reionization depends on the radiative feedback model, f esc, and the environmental overdensity. Our key findings are: (i) for constant f esc models, intermediate-mass galaxies (with halo masses of M_ h10^9-11 M_ and absolute UV magnitudes of MUV ∼ −15 to −20) in intermediate-density regions (with overdensity log10 (1 + δ) ∼ 0−0.8 on a 2 comoving Mpc spatial scale) drive reionization; (ii) scenarios where f esc increases with decreasing halo mass shift, the galaxy population driving reionization to lower mass galaxies (M_ h10^9.5 M_ ) with lower luminosities ( MUV ≳ −16) and overdensities [log10 (1 + δ) ∼ 0−0.5 on a 2 comoving Mpc spatial scale]; (iii) reionization imprints its topology on the ionizing emissivity of low-mass galaxies (M_h10^9 M_ ] through radiative feedback. Low-mass galaxies experience a stronger suppression of star formation by radiative feedback and show lower ionizing emissivities in overdense regions; (iv) a change in f esc with galaxy properties has the largest impact on the sources of reionization and their detectability, with the radiative feedback strength and environmental overdensity playing a sub-dominant role; (v) James Webb Space Telescope -surveys (with a limiting magnitude of MUV = −16) will be able to detect the galaxies providing 60-70 per cent (10 per cent ) of reionization photons at z = 7 for constant f esc models (scenarios where f esc increases with decreasing halo mass).